(untitled) (Research, Society and Development, 2020)
This article aims to relate the contexts of History teaching to countryside education, crossed by the sensitivity of a photographic look turned towards yourself. It is therefore important to observe in the photographic images the experiences of teachers and students in rural environments. This text meets the imagery memories of teachers and communities that reflect a contextualized education from their experiences, taking into account three photographs. The criterion for choosing photographic images was due to the fact that they represent the daily lives of education professionals in the countryside context. At first, we deal with the image as a source of school environment where educational practices of the countryside or rural areas are designed. In the second moment, we approach two images that explore the countryside life where the daily lives of teachers and students happen. And, finally, we approach the Countryside Education as an educational modality with its challenges, persistences, resistances, overcomings and hope for the achievement of a quality education for all. As a result, we observed that the Countryside Education shows itself as a modality of formation in consolidation in which the images of itself and of the rural realities point out didactic possibilities for a knowledge of the Countryside reality.